Capacitance-voltage characterization of commercial gallium nitride diodes subjected to electron radiation - Hedzir, Anati Syahirah; Muridan, Norasmahan; Abdullah, Yusof; Hasbullah, Nurul Fadzlin (Penerbit UMT, Universiti Malaysia Terengganu (UMT), 2016)
The effects of electron radiation on commercially fabricated gallium nitride light emitting diodes (LEDs) is of interest due to its high tolerance against temperature and high breakdown voltage, making it suitable to be used in an extreme environment. LED based on this material is used as part of visible light communication and as an illuminating source in space. However, due to the presence of high energy electron in space, these LEDs are vulnerable towards electron radiation. Hence, this paper focus on the electrical characterization of commercial Gallium Nitride (GaN) LEDs subjected to electron radiation dose ranged from 1MGy to 10MGy. The devices that were used in this study are Kingbright GaN Blue LEDs (part #L-53MBC) and Vishay GaN Blue LEDs (part #TLHB5400). Capacitance-voltage (C-V) characteristics of commercial GaN LEDs before and after irradiation were investigated. As the radiation dose increase, the amount of capacitance and doping concentration decreases. This is believed due to deactivation of dopants atoms in the bulk.